Modelling Fuzzy Analytical Network Process for Sustainability Criteria of Malaysia Higher Education Institutions - Shafi, Roslina Mohamad; Tarmudi, Zamali; Ismail, Norashikin; Zain, Sharifah Raihan Syed Mohd (Advances in Social Sciences Research Journal, 2023)
Sustainable development (SD) plays greater roles in the advancement of Higher Education Institutions (HEI). Yet, criteria for sustainable criteria must be re-defined, specifically in the context of Malaysian HEI. Accordingly, the aim of this study is to identify the sustainability criteria for HEI in Malaysia using Fuzzy Analytical Network Process (F-ANP). Methods used in this study is equipped with Chang’s extent analysis to calculate the local weights for both criteria and sub-criteria based on pairwise comparison evaluations, while the global weights were derived by multiplication operations with the inner dependence weights. Three criteria and nine sub-criteria were identified and analyses thoroughly using six steps of F-ANP for Malaysia HEI sustainability assessment. Based on the numerical results, the sub-criteria “research” scored the highest weights as compared to other sub-criteria, indicating that “research” as the most important contributor to sustain the Malaysia HEI. Meanwhile the total weights score of the overall sub-criteria is 71.60%, which indicates “moderately sustainable” of the entire sustainability range. Overall, the findings suggest that the entire sub-criteria investigated using the extension of AHP are vital in influencing the sustainability of HEI in Malaysia. The study implies that “research” should be given more focus, which in turn leads to greater institutional visibility and reputation.